2014
DOI: 10.1097/bpo.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Capital Realignment Versus In Situ Stabilization for the Treatment of Slipped Capital Femoral Epiphysis

Abstract: Level III retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 41 publications
3
59
1
10
Order By: Relevance
“…Thus, the overall proportion of patients who developed osteonecrosis may be higher than the expected proportion reported by the originators of the technique [13,14,29]. However, all surgeons were experienced in the surgical dislocation approach and the proportion of osteonecrosis in this series compares well to other recent studies [24,25]. We believe that by including multiple surgeons with relevant expertise, we improved the external validity of our study.…”
Section: Discussionmentioning
confidence: 46%
“…Thus, the overall proportion of patients who developed osteonecrosis may be higher than the expected proportion reported by the originators of the technique [13,14,29]. However, all surgeons were experienced in the surgical dislocation approach and the proportion of osteonecrosis in this series compares well to other recent studies [24,25]. We believe that by including multiple surgeons with relevant expertise, we improved the external validity of our study.…”
Section: Discussionmentioning
confidence: 46%
“…Encouraging results with complete restoration of proximal femoral anatomy and low rates of osteonecrosis for stable SCFE have been reported [17,24,26,33,39]. Nevertheless, to our knowledge, only one study has evaluated the modified Dunn procedure versus in situ pinning for treatment of stable SCFE [34]. Souder et al reported a 20% rate of osteonecrosis after the modified Dunn procedure for stable SCFE, however the severity of their cases was not reported [34].…”
Section: Introductionmentioning
confidence: 91%
“…Nevertheless, to our knowledge, only one study has evaluated the modified Dunn procedure versus in situ pinning for treatment of stable SCFE [34]. Souder et al reported a 20% rate of osteonecrosis after the modified Dunn procedure for stable SCFE, however the severity of their cases was not reported [34].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical dislocation has been promoted to treat severe SUFE with a low FHO [33][34][35][36][37] however pooled data from 5 studies (SD) [13,15,[28][29][30] showed a high rate of FHO (25%). This rate was comparable to closed reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of treatments options were reported for the study population including epiphysiodesis [10,11], pinning in situ (PIS) [1,7,[12][13][14][15][16][17][18][19], closed reduction and pinning (CRIF) [4,5,11,15,16,18,[20][21][22][23][24][25], open reduction and physeal osteotomy (PO) [1,7,15,26] open reduction and internal fixation (ORIF) [23][24][25]27] and surgical dislocation (SD) [13,15,[28][29][30].…”
Section: Description Of Studiesmentioning
confidence: 99%